2020
DOI: 10.3389/fpsyt.2020.00018
|View full text |Cite
|
Sign up to set email alerts
|

Duty to Warn: Antidepressant Black Box Suicidality Warning Is Empirically Justified

Abstract: The United States Food and Drug Administration issued a Black Box warning in October 2004 after placebo-controlled trials of antidepressant medications found an increased risk of suicidal thoughts and behaviors among children and adolescents taking antidepressant medications relative to placebo. Subsequently, some researchers have concluded that the Black Box warning caused severe unintended consequences; specifically, they have argued that the warning led to reduced use of antidepressants among youth, which l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 77 publications
0
31
0
1
Order By: Relevance
“…In addition to the methodological issues in accurately estimating the prevalence and magnitude of the problem due to the fact that many trials (especially the older ones) only relied on spontaneous reports of suicidal behavior and/or ideation, we highlight here that, since the warning, there has been a decline in the prescription of antidepressants in young people, alongside an increase in the rate of suicidal events among patients with severe depression ( 4 ). These findings have been criticized by other researchers, which reported data from case-control studies that showed increased risk of suicide attempts and suicide among youth taking antidepressants, even after controlling for some relevant confounders ( 40 ). For clinical practice, one consistent finding from these reviews is that prediction of suicide is difficult and associated with uncertainty.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to the methodological issues in accurately estimating the prevalence and magnitude of the problem due to the fact that many trials (especially the older ones) only relied on spontaneous reports of suicidal behavior and/or ideation, we highlight here that, since the warning, there has been a decline in the prescription of antidepressants in young people, alongside an increase in the rate of suicidal events among patients with severe depression ( 4 ). These findings have been criticized by other researchers, which reported data from case-control studies that showed increased risk of suicide attempts and suicide among youth taking antidepressants, even after controlling for some relevant confounders ( 40 ). For clinical practice, one consistent finding from these reviews is that prediction of suicide is difficult and associated with uncertainty.…”
Section: Discussionmentioning
confidence: 97%
“…While it is possible that the lack of an appropriate diagnosis reflects poor medical practice, we do not have much confidence in our medical record systems to accurately capture treatment decision-making. Reports that emphasize the potential harms of antidepressants, underestimate their potential benefit, and do not acknowledge the lack of any real evidence-based alternatives [5]. Available antidepressants are not perfect, but are much better than the prior generation.…”
Section: Problems With the Current Literature Regarding Antidepressanmentioning
confidence: 99%
“…As of November 26, 2019, Google Scholar indicates this study had been cited 612 times. The Gibbons et al study's finding has thus taken on an air of established truth (4).…”
Section: Introductionmentioning
confidence: 99%
“…Using data from rather poorly designed methodology or cherry-picking data from a time series association between antidepressant prescriptions and suicide rates among youth, some have argued that regulatory warnings caused a decrease in antidepressant prescriptions, which then caused more suicides among youth (4).…”
Section: Introductionmentioning
confidence: 99%